2016
DOI: 10.1080/14767058.2016.1212331
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hyperemesis gravidarum and maternal psychiatric well-being during and after pregnancy: controlled study

Abstract: The results show that mental health is negatively affected by HG at pregnancy, and in this case, psychiatric symptoms may continue even after discontinuation HG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“… 27 . In another study, patients with severe HG in the first trimester, but without prior psychiatric disease, not only presented a negative psychiatric status during pregnancy at the time of HG symptoms, but also had higher risk of PPD 15 . Our results for prolonged nausea are also in line with the study by Meltzer-Brody et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 27 . In another study, patients with severe HG in the first trimester, but without prior psychiatric disease, not only presented a negative psychiatric status during pregnancy at the time of HG symptoms, but also had higher risk of PPD 15 . Our results for prolonged nausea are also in line with the study by Meltzer-Brody et al .…”
Section: Discussionmentioning
confidence: 94%
“…Although the association between NVP and depression has been extensively studied, the literature from large, population-based studies considering the various spectrum of the disease is scarce. Moreover, few studies have taken into account the history of psychiatric disorders 12 and their results are inconsistent 11 , 12 , 14 , 15 . A recent large population-based study on the risk of emotional distress during and after pregnancy, including 92 947 pregnant women, showed that women with HG, defined as prolonged NVP requiring hospitalization before the 25 th gestational week, were more likely to report emotional distress during pregnancy and at six months postpartum, but not at 18 months postpartum compared to women without HG 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been reported high correlations between the Anxiety and Somatization SCL-90-R subscales during the first and second trimester and the Edinburgh Postnatal Depression Scale [ 52 ]. In this respect, recent studies reported the presence of psychopathological symptoms through the SCL-90-R during pregnancy to be related with postpartum depression [ 53 , 54 ]. More specifically, depression, anxiety, and stress during pregnancy have been related with negative pregnancy outcomes, including postpartum depression [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies conducted in Turkey on its use in non-pregnancy related pathologies (38)(39)(40). Two studies were published on its use for the assessment of patients diagnosed with hyperemesis gravidarum in the first trimester of pregnancy from our country (41,42).…”
Section: Discussionmentioning
confidence: 99%